2020
DOI: 10.36552/pjns.v24i2.445
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Decision Making Process on Spine Surgery: Patients’ Perspective

Abstract: Objective:  To determine the factors that affects the decision making process of the spine surgery from a patient’s perspective. Material and Methods:  The study was carried on 264 patients admitted for spine surgery in the Department of Neurosurgery, Khyber Teaching Hospital, Peshawar, Pakistan. Data was collected from patients on questionnaire using a Likert scale. Reliability was ensured by Cronbach alpha. Results:  The results for regression analysis revealed that there is a significant negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
1
0
Order By: Relevance
“…Chand et al had a CSF leak rate of 8.1% and Ghani et al had a CSF leak rate of 12.5%. 19 , 21 It has been found that performing simultaneous shunting while repairing the MMCs has led to significantly reduced rates of CSF leak as well as shorter lengths of hospital stay. 22 …”
Section: Discussionmentioning
confidence: 99%
“…Chand et al had a CSF leak rate of 8.1% and Ghani et al had a CSF leak rate of 12.5%. 19 , 21 It has been found that performing simultaneous shunting while repairing the MMCs has led to significantly reduced rates of CSF leak as well as shorter lengths of hospital stay. 22 …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is advised that the patient and the doctor discuss their options before deciding whether to have surgery. When a patient decides to have surgery, the clinician must share their knowledge and skills with the patient in order to provide the best possible care [ 17 ]. Effective, shared decision-making preferences and interaction between the surgeon and the patient reduce pre-surgery anxiety, help the patient understand the surgical procedure better, and enable them to make informed decisions about their healthcare [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%